2017
DOI: 10.1371/journal.pone.0170438
|View full text |Cite
|
Sign up to set email alerts
|

Acerola (Malpighia emarginata DC.) Juice Intake Suppresses UVB-Induced Skin Pigmentation in SMP30/GNL Knockout Hairless Mice

Abstract: Background/AimsAcerola (Malpighia emarginata DC.) is a fruit that is known to contain high amounts of ascorbic acid (AA) and various phytochemicals. We have previously reported that AA deficiency leads to ultraviolet B (UVB)-induced skin pigmentation in senescence marker protein 30 (SMP30)/gluconolactonase (GNL) knockout (KO) hairless mice. The present study was undertaken to investigate the effects of acerola juice (AJ) intake on the skin of UVB-irradiated SMP30/GNL KO mice.Research design/Principal findingsF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…VC deficiency in humans is referred to as "scurvy," and symptoms include hypoplasia of connective tissue and gums and subcutaneous bleeding. However, recent studies have shown that SMP30/GNL KO mice not only present with scurvy but other symptoms such as underdevelopment, defective hepatic metabolism, and hair growth insufficiency [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…VC deficiency in humans is referred to as "scurvy," and symptoms include hypoplasia of connective tissue and gums and subcutaneous bleeding. However, recent studies have shown that SMP30/GNL KO mice not only present with scurvy but other symptoms such as underdevelopment, defective hepatic metabolism, and hair growth insufficiency [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sulfur-rich extracts such as garlic acid ( Allium sativa in the ERGYTAURINE formulation) may enhance heavy metal removal by inducing antioxidant activities [54,55,56]. Apple pectin [56] and acerole (very rich in vitamin C) also contribute to heavy metals removal [57]. In addition, Sambucus nigra (elderberry) contains antocyanines that supply 87% of the daily vitamin C levels necessary for humans [57].…”
Section: Discussionmentioning
confidence: 99%
“…Apple pectin [56] and acerole (very rich in vitamin C) also contribute to heavy metals removal [57]. In addition, Sambucus nigra (elderberry) contains antocyanines that supply 87% of the daily vitamin C levels necessary for humans [57]. Vitamins B6, B-9, and B-12, as well as Se, Zn ++ , and Mg ++ (ERGYTAURINE formulation) [58] are necessary for certain enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of hydroxyproline, the structural unit of collagen in the skin, markedly decreased after keeping SMP-30/GNL-KO mice in a VC-deficient condition for 60 days. Moreover, skin pigmentation was suppressed when administering VC containing acerola juice followed by UVB irradiation of the skin of VC-deficient hairless mice (6). Other reports regarding the relationship between VC and the skin include a delay in wound healing because of VC deficiency, stimulation of type I collagen gene expression in human skin fibroblasts by VC (7) and VC derivatives, and functional regulation of keratinocytes by the anti-oxidative activity of VC (8).…”
Section: /Gluconolactonase Knockout Mice (Smp-30/gnl-ko) Are a Verymentioning
confidence: 99%